2008
DOI: 10.1158/1535-7163.mct-07-2104
|View full text |Cite
|
Sign up to set email alerts
|

HSP90 inhibitor, DMAG, synergizes with radiation of lung cancer cells by interfering with base excision and ATM-mediated DNA repair

Abstract: Inhibition of heat shock protein 90 (HSP90) leads to inappropriate processing of proteins involved in cell survival pathways. We found that HSP90 inhibitor, 17-(dimethylaminoethylamino)-17-demethoxygeldanamycin (DMAG), is synergistic with radiation for non-small cell lung cancer cell lines, NCI-H460 and A549. To establish the optimal schedule for this combination, cells were radiated before, after, or simultaneously with DMAG, and survival was scored by clonogenic assay. The sequence of DMAG administration was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
53
1
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(65 citation statements)
references
References 34 publications
10
53
1
1
Order By: Relevance
“…Functional tumour suppressor protein p53 was apparently not essential for the radiosensitising action of NVP-AUY922 and NVP-BEP800, because both drugs radiosensitised all tested cell lines, independent of their p53 status (Figures 2 and 3). This finding is consistent with the recent data for two non-small-cell lung cancer cell lines, NCI-H460 and A549 (Koll et al, 2008), but it conflicts with the results for squamous carcinoma cell lines (Shintani et al, 2006), indicating that the Hsp90 inhibitor 17-AAG is a more efficient radiosensitiser in a cell line with p53 wild type compared with four p53-mutated cell lines.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Functional tumour suppressor protein p53 was apparently not essential for the radiosensitising action of NVP-AUY922 and NVP-BEP800, because both drugs radiosensitised all tested cell lines, independent of their p53 status (Figures 2 and 3). This finding is consistent with the recent data for two non-small-cell lung cancer cell lines, NCI-H460 and A549 (Koll et al, 2008), but it conflicts with the results for squamous carcinoma cell lines (Shintani et al, 2006), indicating that the Hsp90 inhibitor 17-AAG is a more efficient radiosensitiser in a cell line with p53 wild type compared with four p53-mutated cell lines.…”
Section: Discussionsupporting
confidence: 87%
“…For that reason, the drugs were used at the same concentration of 200 nM in subsequent experiments. Besides this, the selected drug concentration is consistent with the previously reported 100 nM for 17-DMAG (Robles et al, 2006;Koll et al, 2008).…”
Section: Effects Of Hsp90 Inhibitors On Cell Growth and Radiosensitivitysupporting
confidence: 90%
“…[34][35][36][37] Moreover, HSP90 inhibitors interfere with DNA damage signaling by degrading ATR, Chk1 and Rad51. [38][39][40] Table S1) in the presence of 20 ÎŒM zVAD. The cells were processed as in Figure 4a and representative images are shown.…”
Section: Discussionmentioning
confidence: 99%
“…DNA damage activates ATM through intermolecular autophosphorylation (phospho S1981) and dimer dissociation 40. Inhibition of ATM or pATM (phospho S1981) could radiosensitize cancer cells 20, 41, 42, 43. The present study showed that upregulated miR‐18a‐5p inhibited the expressions of ATM and pATM (phospho S1981) and then enhanced the radiosensitivity of A549 cells and CD133 + stem‐like cells.…”
Section: Discussionmentioning
confidence: 49%